2018
DOI: 10.1016/j.resinv.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the forced oscillation technique in assessing the therapeutic result of tracheobronchial central airway obstruction

Abstract: The FOT is suitable and convenient for assessing therapeutic results in patients with tracheobronchial CAO. The alteration of R20 is useful for estimating the airway dilation of CAO after interventional bronchoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…6 Recently, our previous study revealed that patients with CAO exhibited relatively high values of R5 and R20, Fres, and ALX, and a negative reactance at 5 Hz. 8 In the present study, we first demonstrated the similarities and differences between CAO and COPD, in terms of FOT and PFT parameters. These groups were analyzed with the FOT and PFTs in parallel at one respiratory institute.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…6 Recently, our previous study revealed that patients with CAO exhibited relatively high values of R5 and R20, Fres, and ALX, and a negative reactance at 5 Hz. 8 In the present study, we first demonstrated the similarities and differences between CAO and COPD, in terms of FOT and PFT parameters. These groups were analyzed with the FOT and PFTs in parallel at one respiratory institute.…”
Section: Discussionsupporting
confidence: 51%
“…In that study, airway resistance was measured in patients with CAO; the FOT was applied with the MostGraph-01 (Chest Co., Ltd., Tokyo, Japan) before and after interventional bronchoscopy. 8 We found that the resistance measured at 20 Hz (R20) with the FOT was significantly correlated with the amount of airway dilation achieved with interventional bronchoscopy. 8 To date, no study has directly compared FOT measurements between patients with CAO and those with peripheral airway obstruction, such as COPD.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Another study concluded that the therapeutic results can also be estimated in the case of patients with central airway obstruction using the oscillometric parameter Rrs20. 82 …”
Section: Clinical Applicationsmentioning
confidence: 99%